Industry Sectors Highly Affected by Worksite Outbreaks of Coronavirus Disease, Los Angeles County, California, USA, March 19–September 30, 2020 - Zuelma Contreras; Van Ngo; Marifi Pulido; Faith Washburn; Gayane Meschyan; Fruma Gluck; Karen Kuguru; Roshan Reporter; Condessa Curley; Rachel Civen; Dawn Terashita; Sharon Balter; et al. (Emerging Infectious Diseases, 2021)
Worksites with on-site operations have experienced coronavirus disease (COVID-19) outbreaks. We analyzed data for 698 nonresidential, nonhealthcare worksite COVID-19 outbreaks investigated in Los Angeles County, California, USA, during March 19, 2020‒September 30, 2020, by using North American Industry Classification System sectors and subsectors. Nearly 60% of these outbreaks occurred in 3 sectors: manufacturing (n = 184, 26.4%), retail trade (n = 137, 19.6%), and transportation and warehousing (n = 73, 10.5%). The largest number of outbreaks and largest number and highest incidence rate of outbreak-associated cases occurred in manufacturing. Furthermore, 7 of the 10 industry subsectors with the highest incidence rates were within manufacturing. Approximately 70% of outbreak-associated case-patients reported Hispanic ethnicity. Facilities employing more on-site staff had larger and longer outbreaks. Identification of highly affected industry sectors and subsectors is necessary for targeted public health planning, outreach, and response, including ensuring vaccine access, to reduce burden of COVID-19 in vulnerable workers.